ADAMTS‐4 in oligodendrocytes contributes to myelination with an impact on motor function. Issue 12 (29th August 2017) - Pruvost, Mathilde; Lépine, Matthieu; Leonetti, Camille; Etard, Olivier; Naveau, Mikaël; Agin, Véronique; Docagne, Fabian; Maubert, Eric; Ali, Carine; Emery, Evelyne; Vivien, Denis
Abstract: Myelination is a late developmental process regulated by a set of inhibitory and stimulatory factors, including extracellular matrix components. Accordingly, chondroitin sulfate proteoglycans (CSPGs) act as negative regulators of myelination processes. A disintegrin and metalloproteinase with thrombospondin motifs type 4 (ADAMTS‐4) is an extracellular protease capable of degrading CSPGs. Although exogenous ADAMTS‐4 has been proven to be beneficial in several models of central nervous system (CNS) injuries, the physiological functions of endogenous ADAMTS‐4 remain poorly understood. We first used Adamts4 / LacZ reporter mice to reveal that ADAMTS‐4 is strongly expressed in the CNS, especially in the white matter, with a cellular profile restricted to mature oligodendrocytes. Interestingly, we evidenced an abnormal myelination in Adamts4 −/− mice, characterized by a higher diameter of myelinated axons with a shifting g‐ratio. Accordingly, lack of ADAMTS‐4 is accompanied by motor deficits and disturbed nervous electrical activity. In conclusion, we demonstrate that ADAMTS‐4 is a new marker of mature oligodendrocytes contributing to the myelination processes and thus to the control of motor capacities. Main Points: The expression of ADAMTS‐4 is restricted to mature oligodendrocytes. The lack of ADAMTS‐4 leads to an abnormal myelination and motor deficits.